Effects of olanzapine during cognitive and emotional processing in schizophrenia: A review of functional magnetic resonance imaging findings. (22nd March 2019) - Del Fabro, Lorenzo; Delvecchio, Giuseppe; D'Agostino, Armando; Brambilla, Paolo
Abstract: Objective: Olanzapine is an atypical antipsychotic that is widely used in the treatment of schizophrenia and has shown some degree of efficacy on negative and cognitive symptoms. We aimed to review the effects of olanzapine treatment on brain regions that are directly involved in cognitive and emotional processing. Methods: We used the PubMed database to perform a bibliographic search on functional magnetic resonance imaging studies that investigated the effects of olanzapine treatment on neural activity in patients with schizophrenia during cognitive and emotional tasks. Results: Despite the high variability of tasks and analysis methods employed, the weight of the evidence was consistent with the hypothesis that olanzapine treatment is associated with a normalization of brain activity in schizophrenia. Distinctive functional changes were found in frontal cortex and cingulate cortex activity during both cognitive and emotional tasks. During emotional processing, olanzapine treatment seems to specifically regulate the activity of the striatum and limbic system. Conclusions: The results of the reviewed studies suggest that in patients with schizophrenia, olanzapine treatment might lead to a more physiological brain activity coupled with regulation of dopamine release. Future studies should further corroborate these hypotheses using larger samples and homogeneous experimental tasks.